Social Studies Learning in The Life of The City of Tomb of The Kings With a Structural Functionalism Perspective - Leli Anggreini Ningrum; Ayu Nurhania; Nur Jannah; Dock Chanthoeurn (International Journal of Geography, Social, and Multicultural Education, 2023)
Learning Social Sciences is a multidisciplinary knowledge where one object of discussion can be seen from many social science perspectives. Observation in outdoor learning activities functions as a way to bring real situations to students. Indirectly as a real example of the social sciences being studied, applying essentialism which "says will beat direct touch". This observation includes the Penataran Temple, Karanganyar Coffee Plantation or De Karanganjar Koffieplantage and Bung Karno's Tomb. Interviews were conducted face to face, direct observation by touching and immortalized in the form of photographs which produced qualitative data. Observational data is processed using social science concepts so that it becomes the theme of integrated Social Science learning